Peranan Rekayasa Dalam Sistem Pemanfaatan Kayu Konstruksi di Indonesia - Surjono Surjokusumo; Naresworo Nugroho (Jurnal Ilmu Pertanian Indonesia, 1991)
Up to now the main problem wich always appears in timber construction design is that structural timber is not available readily in the market. A machine stress rating system called PANTER is practical and suitable to the social, economical and technological conditions f the Indonesian way of life, trying to reduce the gap between theory (design) and practice (implementation) of timber construction through structural timber procurement from sawn timber commercial as well as lesser known species in the market. The objective of the study of the role of engineering is to establish a supply system for structural timber in the frame os supporting the realization of a rational timber construction practice. The methodology approach is to identify and study problems related to the producer (sawmill industry) and the construction community (Perumnas or private enterprise) through stress grading activity in the field and to gather secondary data, followed with description and comparative analysis. The result of the study showed that from 2700 pieces of lumber which had been stress graded, consisted of sizes of 5/7, 5/10 and 6/12 cm/cm, were in the range of structural grade TS-7 up to TS-25 (82 %) with the rest of 9 % rejects and only 9 % falls under high strength category (TS-27 up to TS-25). It also was concluded that the stresses in the members produced from the design loadings could be arranged such that each member can function according to a standard size as well as its strength. Optimation using structural timber was achieved through size and stress grade arrangements, such that the needed members of a structural component could be adjusted to the availability of stress grade composition which exist in the field.